Advances in virus research. - Maramorosch, Karl; Shatkin, Aaron J.; Murphy, Frederick A. (Academic Press, 2011)
Published since 1953, Advances in Virus Research covers a diverse range of in-depth reviews providing a valuable overview of the current field of virology. The impact factor for 2009 is 5.522, placing it 2nd in the highly competitive category of virology. * Contributions from leading authorities. Informs and updates on all the latest developments in the field.